Impact of a New Nasal Pillows Mask on Patients' Acceptance, Compliance, and Willingness to Remain on CPAP Therapy - Wimms, Alison (Sleep Disord, 2016)
Aim. Continuous positive airway pressure (CPAP) masks are a key factor in patient compliance. This program assessed the performance of a new nasal pillows mask (NPM) on a variety of new and established obstructive sleep apnea (OSA) patients using CPAP therapy. Methods. Five programs were developed to assess the new NPM [AirFit P10, ResMed] on naïve patients; patients established on another NPM; patients using a nasal mask; patients with low CPAP compliance; and patients who wished to stop using CPAP therapy. Results. A total of 212 patients were included. In naïve patients, CPAP usage after 3 months was 5.9 ± 1.7 hours/night, compared with the control group at 4.6 ± 2.4 hours/night (p < 0.05). In patients established on another NPM, usage improved to 7.4 ± 1.1 hours/night versus 6.7 ± 1.4 (p = 0.001). 78% of nasal mask users wished to continue using the new NPM. Low compliance patients improved with an average of 0.87 hours/night (p = 0.001) when using the new NPM. In patients at the point of quitting CPAP, 60% continued with therapy using the new NPM. Conclusion. The new NPM mask performed well in a variety of clinical groups of OSA patients receiving CPAP therapy and shows that technical advances in CPAP masks can improve patient compliance.